Ultrafast Strong-Field Electron Emission and Collective Effects at a One-Dimensional Nanostructure - Paschen, Timo; Roussel, Ryan; Seiffert, Lennart; Kruse, Björn; Heide, Christian; Dienstbier, Philip; Mann, Joshua; Rosenzweig, James; Fennel, Thomas; Hommelhoff, Peter (ACS Photonics, 2023)
Enhanced near-fields at metallic nanostructures enable the generation of ultrafast nanometric electron pulses and the investigation of fundamental ultrafast dynamics in electron emission. Here we show strong-field induced photoemission from a nanometer-sharp tungsten-covered silicon nanoblade and report the systematic measurement of intensity-dependent electron energy spectra and yields. The observed plateau and cutoff features in the electron spectra indicate the presence of elastic electron rescattering in the enhanced near-fields at the surface of the one-dimensional nanostructure. For the first time, we can hence observe strong-field features from a one-dimensional object, as opposed to zero-dimensional needle tips employed so far. A comparison with results from classical and quantum simulations reveals that the extended geometry of the nanoblades and a cascaded near-field enhancement due to surface roughness leads to a broad energy distribution and high electron energies. A systematic analysis of the electron yield demonstrates nonlinear photoemission at moderate laser intensities and a clear transition to a regime with linear intensity dependence. This distinct feature is interpreted as the onset of space-charge trapping. The presented one-dimensional nanostructure enables us to generate above keV electrons without noticeable target damage and more than 13000 electrons per laser pulse, which is of utmost interest for novel classes of ultrafast photocathodes.
CRIS-Team Scopus Importer:2023-03-03
Keywords: FDTD; one-dimensional; photoemission; space-charge; strong-field; TDSE; ultrafast